EFFECT OF SWIM-UP AND GLASS WOOL TECHNIQUES, WITH ADDING ANTIOXIDANTS TO TRIS EXTENDER ON IMPROVING POST-CRYOPRESERVED SOME SEMEN ATTRIBUTES OF LOW SEMEN QUALITY FOR HOLSTEIN BULLS - Hassan, M. S.; Eidan, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to investigate the effect of swim-up and glass wool as sperm separation techniques with adding vitamin E and superoxide dismutase (SOD) to Tris extender on improving some post-cryopreserved semen quality for Holstein bulls. Low and good of semen were extended using Tris extender. Good semen quality (GSQ) was divided into 3 groups (L1; Tris extender, L2; 2 mM vitamin E, L3; 200 IU SOD) Low semen quality (LSQ) was divided into two main groups, and subdivided into 3 sub-groups (L4; Tris extender, L5; 2 mM vitamin E, L6; 200 IU SOD). In the second main group, swim-up and glass wool techniques were used with adding vitamin E and SOD and subdivided into 3 sub-groups with each technique, and referred to L7, L8 and L9 for swim-up technique and L10, L11 and L12 for glass wool technique. Improving sperms’ cell motility and live sperm and reducing total sperms’ abnormalities percentages of low semen quality were noticed using swim-up and glass wool techniques were used with adding vitamin E and SOD. In conclusion, glass wool filtration separates out dead, abnormal and immotile sperm cells, a good sperm harvested by this technique.